INTERCEPTION AND INFILTRATION OF RAINWATER ON THE LAND OF EX FOREST FIRE ON TAHURA R. SOERJO LEDUG BLOCK - suhermanto, oktavian dwi; Muttaqin, Tatag; Waskitho, Nugroho Tri (Journal of Forest Science Avicennia, 2019)
Forest fires often occur in many islands of indonesia including in Kalimantan, Sumatra, Java, Sulawesi and other regions. These fires can lead to damage for ecosystems, flora and fauna, even ecosystem hydrology. One of the hydrological system that was disturbed is the interception and infiltration. Interception is the ability of trees to retain water rain then rereleased in steam. Infiltration is the process of water absorbing into the soil, infiltration capacity is the soilâ€™s ability of absorbing water per unit of time. This research is to know the rest of the tree's ability to retain water, and knowing the infiltration of ex forest fire area on TAHURA R. Soerjo, Ledug blocks. This research was carried out on 17-23 January 2019 in ex forest fire area on TAHURA R. Soerjo, with an elevation of 1100-1200 masl. In the ex forest fire area there are 2 dominant trees species to do measurements of interception, there are Tutup (Mallotus paniculatus) and Klerek (Sapindus rarak DC). The results of the interception on Klerek tree is 10% and Tutup is 60%. Â For the capacity of the infiltration is 27, 6 mm/hour.Â